Polaron-induced lattice distortion of (In, Ga)As/GaAs quantum dots by optically excited carriers. (13th September 2016) - Tiemeyer, S; Bombeck, M; Göhring, H; Paulus, M; Sternemann, C; Nase, J; Wirkert, F J; Möller, J; Büning, T; Seeck, O H; Reuter, D; Wieck, A D; et al.
Abstract: We report on a high resolution x-ray diffraction study unveiling the effect of carriers optically injected into (In, Ga)As quantum dots on the surrounding GaAs crystal matrix. We find a tetragonal lattice expansion with enhanced elongation along the [001] crystal axis that is superimposed on an isotropic lattice extension. The isotropic contribution arises from excitation induced lattice heating as confirmed by temperature dependent reference studies. The tetragonal expansion on the femtometer scale is tentatively attributed to polaron formation by carriers trapped in the quantum dots.